Respiratory insufficiency and hemoptysis in a patient with dengue: Diffuse alveolar hemorrhage as an unusual presentation of severe dengue - Hurtado-Alegre, Jorge (2022)
Background: Dengue virus infection is an endemic disease in some regions of Peru. Most of these cases are classified as dengue without warning signs and the reported mortality is less than 1%. However, there are certain conditions associated with the disease that could increase mortality. Case report: We present the case of a 48-year-old female patient from a dengue endemic area with clinical and laboratory compatible with dengue disease with warning signs. During hospitalization, she presents hemoptysis and respiratory insufficiency, leading to death. Conclusion: It is important to recognize diffuse alveolar hemorrhage as part of dengue respiratory manifestations and to differentiate it from other infectious and non-infectious possibilities in order to provide appropriate and early management.